AI in marketing : applications, insights, and analysis - Walters, Hannah D.; Hammond, Rachel M. (Routledge, Taylor & Francis Group, 2025)
AI in Marketing equips students with the knowledge to understand the impact of Artificial Intelligence (AI) on marketing strategies, processes, and activities, empowering them to navigate the AI-driven marketing landscape confidently.Divided into four parts, it provides a comprehensive exploration of AI's transformative role in marketing. The first part lays the groundwork, offering foundational insights into the intersection of AI and marketing. Part II explores the various applications of AI in marketing, and the tools marketers use to optimize their processes and deliver enhanced customer experiences. The third part focuses on leveraging AI for consumer insights, enabling marketers to craft data-driven strategies. The final part examines ethical considerations and the pedagogical integration of AI into marketing education. Each chapter includes real-world examples, exercises, discussion questions, key terms, and AI resources, empowering students to develop practical skills and industry-relevant knowledge.Students studying in advanced undergraduate and postgraduate marketing courses will benefit greatly from this comprehensive textbook, preparing them for a future workplace that requires them to know how to use AI effectively, ethically, and responsibly.The book is fully supported by online resources, including an instructor manual and customizable PowerPoint slides.
Keywords: Artificial intelligence -- Marketing applications.; elektronické knihy; electronic books